Management of the Nuris Student Exchange Program in Improving Student Competency at the Leading Madrasah Aliyah Nurul Islam Jember - Rizky Firdausia Rose Ananda; Ahmad Ihwanul Muttaqin (Journal of Islamic Education Research, 2024)
This research explains the management of the Nuris Student Exchange Program in improving student competency at the Leading Madrasah Aliyah Nurul Islam-Jember. This research uses a qualitative approach, with a case study type  Data collection techniques use interviews, observation, and documentation. Data analysis uses data reduction, data presentation, and conclusions/verification. The data validity test was carried out using the triangulation method. The research results show that (1) The Nuris Student Exchange Program planning was carried out by the caretaker board to disseminate Islamic teachings, especially the Aswaja creed. (2) The implementation of the Nuris Student Exchange Program is attended (3) Monitoring and evaluation of the Nuris Student Exchange Program is always carried out with K.H. Muhyiddin, Gus Robith, and other board members. It is for every improvement that we hope that the Nuris Student Exchange Program will be better from year to year.